The Concept of Temporal Agendas in Education - Jan Schiller (Universidade de Lisboa, 2023)
Time and education form a complex relationship that reaches far beyond the trivial fact that education needs time. German discourse in adult and continuing education research rarely focuses systematically on aspects of time. To uncover underlying concepts of time in adult education in policy and practice through the analysis of temporalities, this paper introduces the concept of temporal agendas as an analytical term. Building upon a theory-based reception of temporalities in postmodern society, collective and individual temporal agendas are conceptualised. A methodological approach to the inquiry of temporal agendas is outlined based on a recent research example and highlighting the importance of sectoral temporal orders. Finally, a brief outlook into possible future research on temporal agendas in important educational developments is given.